Medication self-management in patients with epilepsy: a narrative review of current status, influencing factors, and intervention strategies - Wang, Huayuan; Liu, Xinmin (Frontiers in Neurology, 2025)
The contribution of medication management to epilepsy treatment has been demonstrated in numerous studies. However, existing research has primarily focused on improving patient medication adherence and optimizing medication regimens by healthcare teams, lacking a systematic review of the current state of medication self-management from the patient perspective. This paper systematically reviews published research in the field of medication self-management among epilepsy patients, elucidating the concept of medication self-management, its current challenges, influencing factors, and advances in intervention strategies. The study concludes that a multidimensional intervention system integrating individual characteristics, technological empowerment, and systemic support must be established in the future. The efficacy of interventions should be validated through large-scale, long-term studies, while advancing the human-centered design of technological tools to achieve inclusive and precision-driven development in global epilepsy management.